Ag3PO4 electrocatalyst for oxygen reduction reaction: enhancement from positive charge. Issue 10 (31st January 2018) - Qin, Yong; Li, Fan; Tu, Peng; Ma, Yanling; Chen, Wenlong; Shi, Fenglei; Xiang, Qian; Shan, Hao; Zhang, Lifu; Tao, Peng; Song, Chengyi; Shang, Wen; et al.
Abstract : Ag3 PO4 nanoparticles are active ORR catalysts. DFT calculation revealed better ORR performance of Ag atom on the surface of Ag3 PO4 due to its enhanced O2 adsorption. The highest ORR activity on {110} surface of rhombic dodecahedral Ag3 PO4 is 12 times active as Pt catalysts. Abstract : We have demonstrated Ag3 PO4 as an active non-Pt electrocatalyst with enhanced activity compared with Ag for oxygen reduction reaction (ORR). Density functional theory reveals that better ORR performance of Ag atoms on Ag3 PO4 surface than that on pure silver surface originates from more appropriate oxygen adsorption on positively charged Ag atoms. Further study of the surface geometry of Ag3 PO4 including tetrahedron, rhombic dodecahedron and cube indicates that the highest density of Ag and appropriate oxygen adsorption on {110} surface of rhombic dodecahedral Ag3 PO4 lead to the highest ORR activity, which is about 12 times that of Pt catalysts from a commercial perspective. It may be applicable for developing low-cost and highly active non-Pt catalytic materials from a broader range of material systems.